Risk factors for radiation‐induced optic neuropathy: a case–control study. (9th March 2017) - Ferguson, Ian; Huecker, Julie; Huang, Jiayi; McClelland, Collin; Van Stavern, Gregory
Abstract: Importance: Identifying risk factors for radiation‐induced optic neuropathy (RION) could promote a more conservative approach to radiation treatment planning in vulnerable patients. Background: This study explored possible factors beyond radiation dose associated with the development of RION after external beam radiation therapy. Design: This was a retrospective case–control study conducted at a university hospital tertiary care center. Participants: Cases ( n = 14) meeting criteria for a diagnosis of RION by neuro‐ophthalmologic exam were identified from a single‐centre neuro‐ophthalmology database. Controls ( n = 31) without RION were selected from a single‐centre radiation oncology database. Methods: Controls were matched to cases based upon maximum radiation dose to the optic apparatus. Patient characteristics and treatment parameters were interrogated by univariate analysis for attributes predisposing to RION. Main Outcome Measures: The primary parameter was a significant association of patient characteristics or treatment parameters with RION. Results: Controlling for radiation dosage, no significant associations for alternative risk factors were identified. Conclusions and Relevance: These results support the literature suggesting that the primary risk factor for developing RION is radiation dosage and that additional patient‐related and tumour‐related risk factors may play only a minor role.